Helicobacter pylori Infection and Childhood Recurrent Abdominal Pain: Lack of Evidence for a Cause and Effect Relationship - Colin Macarthur (Canadian Journal of Gastroenterology)
BACKGROUND: Recurrent abdominal pain is a common complaint among children and adolescents. Apley’s criteria – at least three discrete episodes of abdominal pain of sufficient severity to interrupt normal activities that occur over a period of three or more months - are often used to define this chronic pain syndrome.